Spaces of uneventful disaster tracking emergency housing and domestic chemical exposures from New Orleans to national crises - Shapiro, N (2014)
In this thesis, I examine the politics, poetics, and logics of uneventful human harm in the United States by tracking the life and afterlife of a chemically contaminated emergency housing unit. In 2005, the Federal Emergency Management Agency (FEMA) deployed 120,000 trailers to the US Gulf Coast to house those displaced by Hurricanes Katrina and Rita. Chemical testing, spurred by reports of inhabitant illness, revealed elevated levels of formaldehyde emanating from the plywood walls of the trailers. After being reclaimed by the federal government and beginning in 2010, the FEMA trailers were resold at auction to every corner of the country. Resold trailers gravitated to precarious populations at the poles of rural capital accumulation—from oil patches in North Dakota to reservations in Washington. These trailers serve as an exceptional substrate for an investigation into the anatomy of the uneventful as they once approached the apex of eventfulness as a national controversy and now reside in the shadows of the everyday. This thesis apprehends and theorizes these dispersed and ordinary instruments of domestic harm across multiple registers: epistemological, material, spatial, and affective. I examine how failures of matter and meaning shaped and patterned the lives of those who inhabited the FEMA trailers as their lives became framed by chemical off-gassing, architectural insufficiency, material deterioration, and electrical short-circuiting. Crossing scales and venues, I interrogate the modalities of scientific incomprehension that erode the perception, admittance, or substantiation of mass chemical exposure. These technical processes, along with cultural horizons of eventfulness and the chronicity of disaster, foreclosed avenues of toxic harm accountability. These ‘economies of abandonment’ bring into relief the contemporary biopolitical priorities in which the FEMA trailer—an ostensible protection from harm that fosters illness—becomes possible. FEMA trailer residents attend to the minute, gradual, and ongoing symptoms of exposure to discern the reality and magnitude of residential contamination. The body of the exposed becomes both an epistemic instrument and, across time, the means of making low-level, chronic, and cruddy chemical exposures into eventful instances that drive individuals to action.